Determination of harpagoside in Harpagophytum procumbens DC tablet’s using analytical method by High Performance Liquid Chromatography - Ribeiro, Gislane dos Santos; Carneiro, Amanda de Assis; Martins, Diegue Henrique Nascimento; Simeoni, Luiz Alberto; Silveira, Dâmaris; Magalhães, Pérola Oliveira; Fonseca-Bazzo, Yris Maria (Eclética Química, 2020)
The species Harpagophytum procumbens DC. is popularly known as devil’s claw and is widely used because of its anti-inflammatory properties that are attributed to an iridoid glycoside, the harpagoside. This medicinal plant is part of the Brazilian List of Essential Medicines, that is, it was selected and standardized for the resolution of diseases in the Brazilian public health system, SUS, and can be found in several brands. Due to the importance of quality monitoring, the objective of this study was to create and validate a method for identification and quantification of harpagoside in tablets of the devil’s claw, as well as to evaluate the content of this iridoid glycoside in three commercially available brands in Brasília, DF, Brazil. The evaluated parameters in the validation by high performance liquid chromatography (HPLC) were linearity, limits of detection and quantification, precision, selectivity, accuracy and robustness, as required by the Brazilian regulation. The developed and validated method proved satisfactory for the quality control of commercial products that present in this composition the medicinal plant. All the devil’s claw brands presented divergences regarding the quality that can interfere with therapeutics and with safety and efficacy.